Pathways and the sound of crackling twigs: the challenge of university press publishing - Geraldo, Sheila Cabo (PORTO ARTE: Revista de Artes Visuais, 2013)
The article raises some discussions about scholarly publications in the field of arts presenting the journals as special places to make public art criticism and questioning their suitability for academic parameters, which often preclude the journals to develop his true vocation.